Effects of Working Memory Capacity and Cognitive Load on Decision Making and Rational-Experiential Information Processing - Çepelioğullar, Nilgün (My University, 2025)
Decision making is a situation that we encounter everyday. we come across theories supporting that we make decisions based on intuitions against the theories supporting that we make a decision by evaluating the possible results of the choices. Working memory has an important part in remembering the results of previous decisions and evaluating the consequences and studies are made to examine the relation between the two. Any load that limits working memory capacity effects decision making outcomes. The fact that there are two groups of theories that support rational or intuitive decision making has led to the investigation of relation between rational-experiential information processing and decision making. Yet studies investigate these relations separately. In the current study, the effect of cognitive load on information processing strategy and the way which it alters decision making is examined. Results show a significant relationship between working memory capacity and rational information processing, but no such relationship is found to be significant in relation to experiential processing as excepted. Cognitive load had a significant main effect on decision making and rationality but had no effect on experientiality. Results are discussed in accordance with relevant literature.
Keywords: Decision making; Working memory capacity; Rational-experiential information processing; Cognivite load